ANALYSIS OF FINANCIAL REPORTING PLATFORMS BASED ON THE PIPRECIA-S METHOD - Mladenovic, Marija; Đukić, Tijana; Popovic, Gabrijela (Journal of process management and new technologies, 2023)
Effective financial reporting is crucial for both regulatory compliance and well-informed decision-making in today's dynamic corporate climate. To streamline their financial reporting procedures, numerous businesses rely on various financial reporting platforms. This paper gives a case study that looks at how four firms implemented and used financial reporting tools such Microsoft Excel, SAP ERP, Host Analytics, and QuickBooks. According to the study's findings, using contemporary platforms has increased accuracy and efficiency. Additionally, the study highlights how vital it is to continuously adapt and embrace new technology in order to guarantee that financial reporting continues to be a benefit for businesses of all shapes and sizes. Finally, it makes a strong case for utilizing contemporary financial reporting tools to improve the accuracy and efficiency of financial reporting procedures. To make sure they are optimizing the advantages of financial reporting, organizations should place a high priority on remaining current with technological developments.